The AIMS approach: regulating receptivity in patient-provider vaccine conversations - Parrish-Sprowl, John; Thomson, Angus; Johnson, Rodger D.; Parrish-Sprowl, Susan (Frontiers in Public Health, 2023)
The World Health Organization named vaccine hesitancy a leading global health threat of modern time. Addressing this public health issue requires a multi-front strategy, one such strategic effort is training health care professionals to respond to reluctant patients/parents or those who refuse vaccines. AIMS (Announce, Inquire, Mirror, and Secure) is designed to help HCPs engaged in more productive conversations with patients/parents to secure trust, a key behavior leading to higher vaccination rates.